Challenges in the Treatment of Restless Legs Syndrome: A Case Report - Audrey Umbreit; Shirshendu Sinha; Bhanu Prakash Kolla; Meghna P. Mansukhani (Journal of Primary Care & Community Health, 2021)
Treatment resistant restless legs syndrome (RLS) in the setting of psychiatric comorbidities can be difficult to manage. Our patient is a 69-year-old Caucasian gentleman with bipolar disorder type I, unspecified anxiety disorder, obstructive sleep apnea (OSA), and treatment-refractory RLS. At initial presentation, the patient’s prescribed medication regimen included fluoxetine 40 mg daily, gabapentin 800 mg in the morning and 3200 mg at bedtime, pramipexole 0.375 mg daily, lamotrigine 200 mg daily, trazodone 200 mg at bedtime, and temazepam 15 to 30 mg as needed for insomnia and RLS. Over the course of nearly 4 years, treatment interventions for this patient’s RLS included: cognitive behavioral therapy for insomnia, discontinuation of exacerbating medications, switching dopamine agonists, use of pregabalin and iron supplement. This report demonstrates a challenging case of RLS in the setting of psychiatric comorbidities, development of augmentation, and polypharmacy.